Modifikasi Pukis dengan Penambahan Tepung Gaplek dan Daun Melinjo sebagai Kudapan Tinggi Serat Gaplek - Shupiyyah, Shupiyyah; Nuraeni, Ani (Jurnal GIZIDO, 2024)
Gaplek flour and melinjo leaves are food ingredients with good nutritional content, one of which is high in fiber. High fiber in foods including snacks can help prevent central obesity in adolescents. This study aims to analyze consumer acceptance of the addition of cassava flour and melinjo leaves to pukis. The research procedure starts from procuring cassava flour, melinjo leaves, chicken seasoning balado, processing the pukis formulation, hedonic test, analyzing the nutritional content of the selected formula, calculating the %ALG of the selected formula, and analyzing production costs. Pukis F1 (40% wheat flour: 60% gaplek flour + 40% melinjo leaves) was determined as the selected formula based on the hedonic test results. Pukis F1 in 100 g contains 243 cal energy, 14,5 g protein, 6,1 g fat, 42,5 g carbohydrate, and 18,5 g dietary fiber. Pukis with the addition of gaplek flour and melinjo leaves per serving (45 g) contributed 6% energy, 11% protein, 4% fat, 6% carbohydrate, and 28% dietary fiber.